2006
DOI: 10.1063/1.2207501
|View full text |Cite
|
Sign up to set email alerts
|

In situ and real time determination of metallic and semiconducting single-walled carbon nanotubes in suspension via dielectrophoresis

Abstract: We report an alternative method combining dielectrophoresis and impedance spectroscopy to provide rapid, accurate measurement of dielectrophoretic collection of single-walled carbon nanotubes ͑SWNTs͒ in real time. We analyzed a Triton X-100 suspension of mixed SWNTs to measure their precise dielectrophoretic collection behavior. Results indicate that our sample contains 21.5% of metallic and 78.5% of semiconducting carbon nanotubes before separation, and that the range of 1 -15 MHz is ideal to collect only the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…By mapping the variation of τ as a function of frequency (but with constant particle concentration) it is possible to determine the DEP collection rate of the particles. This technique was originally developed for carbon nanotubes 16 and nanowires, 19 where it was found that conduction around the electrical double layer 20 dominated the DEP response of particles in this size regime.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By mapping the variation of τ as a function of frequency (but with constant particle concentration) it is possible to determine the DEP collection rate of the particles. This technique was originally developed for carbon nanotubes 16 and nanowires, 19 where it was found that conduction around the electrical double layer 20 dominated the DEP response of particles in this size regime.…”
Section: Discussionmentioning
confidence: 99%
“…16,19 The inverse of the time constant was then used to approximate the DEP force, as collection rate is inversely proportional to the force causing the particles to collect. Figure 2 shows the inverse time constant for two medium conductivities, 1.1 and 100 mS/m.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model used here is based on an advancement of the work of Irimajiri (1979) by Broche (2005) and considers a cell to be a homogenous sphere (the cytoplasm) suspended in a second sphere (the cell wall) which is in turn surrounded by the suspending medium. Other models for non-spherical geometry such as ellipsoids or rods are reported in the literature and can be used to model particles such as red blood cells (Jones 1995), elongated bacteria (Sanchis et al, 2004;Castellarnau et al, 2006) or carbon nanotubes (Mureau et al, 2006). Various algorithms and programs for computer models are published as well (Hughes 2002;Morgan and Green 2003).…”
Section: Dielectrophoresismentioning
confidence: 99%
“…Therefore, their applications are relatively limited. By comparison, dielectrophoresis, a simple but versatile method, has proven to be effective in aligning CNTs in small and large scales (Gultepe et al, 2008;Mureau et al, 2006). This method can be conducted at room temperature with low voltages.…”
Section: Introductionmentioning
confidence: 99%